Utilization of Bamboo fibre and M-sand in Concrete as a Replacement of Natural Sand : A Review - Gour, Deep Singh; Prasad, Bikram (International Journal of Scientific Research in Civil Engineering, 2020)
In the current world, concrete has become a very important part of the construction industry and the materials which are used in making concrete have evolved due to better quality of cement and better grade of coarse aggregates. The sand is an important part of concrete. It is mainly procured from natural sources. Thus the grade of sand is not under our control. The concrete cubes of M-25 grade were threw in this trial explore work and tried to analyze different properties of concrete like compressive quality, workability. In this study we are reviewing literatures related to advances in concrete technologies, and utilization of fibers and materials in construction industry.
Keywords: Concrete; Fibers; Compressive Strength; Flexure Strength; Improvement; Grade